ARXPS measurement simulation for improved data interpretation at complex Ta/Li‐niobate interfaces1. (21st March 2014) - Oswald, S.; Vogel, U.; Eckert, J.; Abel, Marie‐Laure; Rossi, Antonella; Watts, John F.
<x xml:space="preserve">Abstract</x> For surface acoustic wave devices, piezoelectric substrates have to be coated with barrier and metallization layers. The interface formation plays an important role for the functionality of the layer systems. We used angle‐resolved XPS for nondestructive interface characterization of such material systems. However, the analyses are challenging for complex systems as considered here, because model calculations always have to be performed for data interpretation. To eliminate measuring uncertainties, in a first step, Monte Carlo simulations of angle‐resolved XPS measurement were performed. By use of such reliable data, system inherent uncertainties can be revealed. It is shown that the application of appropriate boundary conditions is inevitable the more complex the structures are. The use of high (near‐surface) measuring angles is discussed as one possible advantageous way. Copyright © 2014 John Wiley & Sons, Ltd.